2012
DOI: 10.1123/jsep.34.5.621
|View full text |Cite
|
Sign up to set email alerts
|

Further Validation and Development of the Movement Imagery Questionnaire

Abstract: This research validated and extended the Movement Imagery QuestionnaireRevised (MIQ-R; Hall & Martin, 1997). Study 1 (N = 400) examined the MIQ-R's factor structure via multitrait-multimethod confirmatory factor analysis. The questionnaire was then modified in Study 2 (N = 370) to separately assess the ease of imaging external visual imagery and internal visual imagery, as well as kinesthetic imagery (termed the Movement Imagery Questionnaire-3; MIQ-3). Both Studies 1 and 2 found that a correlated-traits corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
152
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 192 publications
(171 citation statements)
references
References 51 publications
14
152
0
5
Order By: Relevance
“…However, that study was conducted in one specific sport discipline, basketball, and the group of respondents was not large (n = 62, 31 females and 31 males). Our research confirmed that gender differences do not exist in movement imagery ability, as in the original study (Williams et al, 2012). There was no significant correlation between age and imaging visual and kinesthetic abilities, which corresponds to previous studies on the general imagery ability (Budnik-Przybylska, 2014;Bhasavanija et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, that study was conducted in one specific sport discipline, basketball, and the group of respondents was not large (n = 62, 31 females and 31 males). Our research confirmed that gender differences do not exist in movement imagery ability, as in the original study (Williams et al, 2012). There was no significant correlation between age and imaging visual and kinesthetic abilities, which corresponds to previous studies on the general imagery ability (Budnik-Przybylska, 2014;Bhasavanija et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…With regard to gender the results were in line with previous studies, which indicated gender invariance in the imagery ability (Campos, 2014;Williams et al, 2012;Bhasavanija, Vongjaturapat, Morris, & Muangnapo, 2011;Hall, 2001;Richardson, 1994Richardson, , 1999Abma, Fry, Li, & Relyea, 2002;Lorant & Nicholas, 2004;Vadocz, Hall, & Moritz, 1997). Despite the fact that there was some evidence where males and females presented different imagery generating capabilities, it should be pointed out that different aspects of imagery were examined and only limited differences were discovered (Ozel, Molinaro, & Larue, 2001;Richardson, 1995;Taktek, 2004;Campos, Pérez-Fabello, & Gómez-Juncal, 2004;Williams & Cumming, 2011;Budnik-Przybylska, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A higher score therefore represents a higher ability to perform visual or kinesthetic imagery. Williams et al (2011) identified the MIQ-3 to be a valid and reliable questionnaire.…”
Section: Methodsmentioning
confidence: 99%